Penerjemahan Majas Personifikasi Dalam Novel Sekai No Chuushin De Ai Wo Sakebu Karya Katayama Kyoichi - Jessica Pratiwi, Ni Luh (Humanis, 2017)
This research’s titled is “The Translation of Personification in Sekai no Chuushin de Ai wo Sakebu by Katayama Kyoichi”.  The objective of this research is to know the types of personification and the translation strategies.  This research used the types of personification teory by Tsutomu (2005) and the translation strategies by Larson (1998). Result of this research show that there are four types of personification in Sekai no Chuushin de Ai wo Sakebu Novel by Katayama Kyoichi such as meishiku gijinhou, doushiku gijinhou, keiyoushiku gijinhou, and fukushiku gijinhou. Moreover, the translation strategy personification translation are used in  three strategies.